Строптивая мишень: [повесть] / Татьяна Полякова - Полякова Татьяна (Авантюрный детектив, 2011)
Экземпляры: (20220531) / Инвентарный номер: 36494 / Цена: 576.45 / Сис.шифр: 84(2=411.2)6 / Авт.знак: П 54 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6